Smart Parking and Weather Monitoring System - Prof. D G Chougule; Rukhsar Sattar Shaikh; Prof. A. S. Mali (International Journal of Engineering and Management Research, 2023)
Every vehicle faces a parking situation, As the number of people has increased, the number of vehicles on the road also increased . Increasing the number of vehicles in cities has lead to problem of finding the parking space in public areas. In metro Cities during peak hours drivers faces real problem of finding parking space . At instant Drivers are not knowing where the parking spaces are available, this causes them parking difficulty. To resolve this problem I have developed a system using Internet of Things (IOT) ,sensors, At mega 328 micro controller, and thinkspeak application. In this study we design a smart parking system with weather monitoring which enables the user to give availability of parking slots in advanced before reaching to that respective parking area , the system also deals with monitoring the environmental conditions like temperature, rain , humidity, air quality etc. This system will reduce the time in finding the parking lots and also will avoids the unnecessary travelling through filled parking lots in a parking area thereby reducing the fuel consumption which in turn will help reduces carbon footprints in atmosphere.